High dose of ascorbic acid induces selective cell growth inhibition and cell death in human gastric signet-ring cell carcinoma-derived NUGC-4 cells - Saitoh, Yasukazu; Takeda, Kaori; Okawachi, Koichi; Tanimura, Yusuke (Biochimica et biophysica acta. General subjects, 2025)
Anticancer effects of high-dose vitamin C (VC) have been evaluated on many cancer cell lines, and its efficacy in clinical trials and in combination with anticancer drugs or radiation have been reported; however, its effect on gastric cancer and its mechanisms remain unclear. In the present study, the cell growth inhibitory/lethal effects of high-dose ascorbic acid (AsA), a reduced form of VC was examined on three gastric cancer cell lines. Of these, signet ring cell carcinoma NUGC-4 cells were the most sensitive, but the effects were small and limited in normal cells. Second, high-dose AsA was effective in NUGC-4 cells, whereas dehydroascorbic acid, an oxidized form of VC, was less effective. Third, high-dose AsA showed stronger cell growth inhibitory/lethal effects on floating cells than on adherent cells, and was effective even under hypoxic microenvironment conditions. A single 1-h treatment of high-dose AsA strongly inhibited cell growth, causing apoptosis-like cell death over 72 h after treatment, triggered by hydrogen peroxide generation, actin abnormality, DNA synthesis suppression, DNA damage induction, and ATP level decrease. The effects of high-dose AsA were inhibited either by adding or chelating iron ions, but was not affected via inhibiting AsA transport. Inhibition of glutathione synthesis enhanced the anticancer effects of high-dose AsA. These results indicate that a single high-dose of AsA induces cancer cell-selective, sustained cell growth inhibition and cell death, and these effects may be regulated by iron ion and/or intracellular oxidative stress levels in human gastric signet-ring cell carcinoma-derived NUGC-4 cells. [Display omitted] •High-dose ascorbic acid exerts anticancer effects in gastric signet-ring cells.•Single high-dose of ascorbic acid induces sustained cell growth inhibition.•It induces actin abnormalities, changes cell morphology, and DNA damage.•Oxidative stress and iron ion levels act as regulators for the anticancer effects.